Eukaryotic Translation Initiation Factor eIFiso4G Is Required to Regulate Violaxanthin De-epoxidase Expression in Arabidopsis - Chen, Zhong (American Society for Biochemistry and Molecular Biology, 2014)
The eukaryotic translation initiation factor (eIF) 4G is a scaffold protein that organizes the assembly of those initiation factors needed to recruit the 40 S ribosomal subunit to an mRNA. Plants, like many eukaryotes, express two eIF4G isoforms. eIFiso4G, one of the isoforms specific to plants, is unique among eukaryotic eIF4G proteins in that it is highly divergent and unusually small in size, raising the possibility of functional specialization. In this study, the role of eIFiso4G in plant growth was investigated using null mutants for the eIF4G isoforms in Arabidopsis. eIFiso4G loss of function mutants exhibited smaller cell, leaf, plant size, and biomass accumulation that correlated with its reduced photosynthetic activity, phenotypes not observed with the eIF4G loss of function mutant. Although no change in photorespiration or dark respiration was observed in the eIFiso4G loss of function mutant, a reduction in chlorophyll levels and an increase in the level of nonphotochemical quenching were observed. An increase in xanthophyll cycle activity and the generation of reactive oxygen species contributed to the qE and qI components of nonphotochemical quenching, respectively. An increase in the transcript and protein levels of violaxanthin de-epoxidase in the eIFiso4G loss of function mutant and an increase in its xanthophyll de-epoxidation state correlated with the higher qE associated with loss of eIFiso4G expression. These observations indicate that eIFiso4G expression is required to regulate violaxanthin de-epoxidase expression and to support photosynthetic activity.